Recadoration of Political Parties Preparation of General Elections in the Perspective of Caderization Theory - Mardiana Mardiana; Mugeni Murdian Hasyim; Abdul Rasyid Ridha; M. Reza Fahlevi; Muzahid Akbar Hayat (Scholar Center, 2022)
Examine the cadre formation of political parties in preparation for general elections in the perspective of cadre theory.This study aims to how is the dynamics of cadre formation of political parties in Indonesia and what is the effect of cadre formation of political parties on the progress of the country through elections in the perspective of cadre formation. This research is a type of qualitative research, the nature of prescriptive research. The results of this study indicate that improving the quality of regeneration is a must in solving various problems within the organization. The need to increase the cadre mechanism in accommodating the cadre of existing political parties in Indonesia for political parties as a forum for cadres and forerunners of power holders in the executive and legislative.